Raw water reserve and conveyance capacity of West Water Canal of Metropolitan Waterworks Authority - J. Nirunrat; W. Thaisiam; A. Pornprommin (International Association of Lowland Technology, 2018)
Metropolitan Waterworks Authority (MWA) is responsible for supplying potable water to Bangkok, Nonthaburi and Samut Prakan provinces. There are two raw water sources used, Chao Phraya River and Mae Klong River, conveyed via canal systems. At present, West Water Canal (WWC) system with the total length of 107 km carrying the discharge of about 20 m3/s from Mae Klong River. It was designed to be capable to convey 45 m3/s with using Bang Len Pumping Station (71 km from the upstream end). However, MWA modified the WWC system by constructing a bypass canal at the pumping station. Thus, water flows completely by the gravitation which saves both cost and energy. Nevertheless, it is expected that the present canal system cannot deliver water at its design conveyance capacity, and problems may arise in the future if water demand increases. In this study, we have performed a fully hydrodynamic onedimensional model. It is found that the present maximum capacity is approximately 24 m3/s. To meet the design capacity of 45 m3/s without using the pumping station, it is necessary to implement 15-km canal modification and build an additional bypass canal. The redesign of the canal will help MWA to save the energy at least 4,750 Mwh/year. In addition, it should be known that how long and how much we can use water reserve in the canal for production if the inlet at Mae Klong River is temporally closed due to emergency or canal maintenance. From the model result, WWC system can reserve water for 15 and 12 hours for the cases of the existing system under 24 m3/s and the modified system under 45 m3/s, respectively.